OPTIMALISASI PEMASARAN DIGITAL UNTUK MENINGKATKAN DAYA SAING UMKM KEDUNGJAMBE - Tiara Meyla Seibinna; Maharani Ikaningtyas (Cahaya Ilmu Bangsa, 2025)
This study aims to analyze strategies for optimizing digital marketing to enhance the competitiveness of Kedungjambe MSMEs. MSMEs play a significant role in the national economy, but challenges such as the COVID-19 pandemic and limited adoption of digital technology hinder their potential. Using a qualitative approach, this research identifies barriers and opportunities for MSMEs to compete in the global market. The findings reveal that optimizing digital marketing, including the use of social media, e-commerce, and personalized services, can significantly enhance MSME competitiveness. Recommendations are provided to support MSME digital transformation, including training, mentoring, and digital infrastructure development. This research is expected to serve as a reference for policy development to empower MSMEs in the digital era.